Improving primary care access for rural women Veterans: the Boost Team - Cohen, Jenny K.; Monteith, Lindsey L.; Stacker, Tara; McCarthy, Michaela; Bomsztyk, Mayan; Wilson, Abigail; Childers, Jennifer; Hussain, Tanvir; Kohlwes, Jeffrey (Frontiers in Health Services, 2024)
ObjectivesTo improve healthcare access for rural cisgender women and gender diverse Veterans, we created the “Boost Team,” a clinician-driven telehealth outreach service to connect this population to Veterans Health Administration (VHA) services.MethodsBetween 9/2021 and 2/2022, we conducted a needs assessment in the Veterans Integrated Service Network (VISN) 21 and used those data to develop an outreach intervention. We piloted a clinician-led outreach intervention in 3/2022, and formally deployed an outreach team in 9/2022.ResultsThe needs assessment uncovered opportunities to educate Veterans, staff, and clinicians about available VHA women's health services, and a need for easily-accessible gender-sensitive services. During the pilot, 58% (7/12) rural cisgender women Veterans were successfully contacted, all reported positive experiences with the intervention. The formal outreach team launched in 9/2022 and consists of a nurse practitioner (NP), scheduler, Peer Support Specialist, and medical director. From 9/2022 to 12/2022 the Boost NP called 110 rural cisgender women and gender diverse Veterans and spoke to 65 (59%) of them. Common care needs identified and addressed included care coordination, new referrals, medication management, and diagnostics.DiscussionData from Boost show that clinician-led outreach can engage rural cisgender women and gender diverse Veterans in VHA services, there is a desire for more gender-sensitive services, and there is a need for systems-level improvements to allow for improved care coordination and decreased leakage outside of VHA. Using robust strategies grounded in implementation sciences, we will continue conducting a program evaluation to study the impact of Boost and scale and expand the program.